Multiple inappropriate implantable cardiac defibrillator therapies in rapid succession. Issue 12 (23rd October 2017) - Marbach, Jeffrey A.; Yeo, Colin; Green, Martin S.; Nair, Girish M.
Key Clinical Message: Inappropriate implantable cardiac defibrillator (ICD) shocks are associated with significant morbidity and have the potential to trigger ventricular arrhythmias, cardiac decompensation, and death. We present a case of multiple inappropriate ICD therapies in rapid succession due electromagnetic interference from a Dr‐Ho's transcutaneous electric nerve stimulator machine, and subsequently from a faulty electrical outlet. Abstract : Inappropriate implantable cardiac defibrillator (ICD) shocks are associated with significant morbidity and have the potential to trigger ventricular arrhythmias, cardiac decompensation, and death. We present a case of multiple inappropriate ICD therapies in rapid succession due electromagnetic interference from a Dr‐Ho's transcutaneous electric nerve stimulator machine, and subsequently from a faulty electrical outlet.